2022
DOI: 10.1007/s00586-022-07135-9
|View full text |Cite
|
Sign up to set email alerts
|

FUSE-ML: development and external validation of a clinical prediction model for mid-term outcomes after lumbar spinal fusion for degenerative disease

Abstract: Background Indications and outcomes in lumbar spinal fusion for degenerative disease are notoriously heterogenous. Selected subsets of patients show remarkable benefit. However, their objective identification is often difficult. Decision-making may be improved with reliable prediction of long-term outcomes for each individual patient, improving patient selection and avoiding ineffective procedures. Methods Clinical prediction models for long-term function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Of the 31 CDSS studies reviewed, 11 (35%) prognostic CDSS studies ( Table 4 ) were knowledge based [ 44 , 45 , 47 - 54 , 59 ], with regression-based predictive algorithms. White-box models were used across all studies; most CDSSs were presented as web-based calculators, whereas others were presented as independent software.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 31 CDSS studies reviewed, 11 (35%) prognostic CDSS studies ( Table 4 ) were knowledge based [ 44 , 45 , 47 - 54 , 59 ], with regression-based predictive algorithms. White-box models were used across all studies; most CDSSs were presented as web-based calculators, whereas others were presented as independent software.…”
Section: Resultsmentioning
confidence: 99%
“…17,18,22,[30][31][32] The format of an online calculator renders complex statistical models more accessible with the potential for broad clinical impact. 17,18,22,[30][31][32] The HOPS calculator thus builds on the previously reported HOPS study, which identified five important predictors of post-hemispheric surgery seizure freedom (age greater than 3.5 years at seizure onset, absence of generalized seizure semiology, absence of contralateral FDG-PET hypometabolism, stroke-induced seizure etiology, and absence of prior resective neurosurgery) and developed an easyto-use seizure outcome prediction score. 1 As a result, this online calculator renders the original prediction tool readily and widely used by clinicians to estimate the potential benefits of hemispheric surgery in a given patient into a tool that epilepsy centers and families worldwide can access, utilize, and comprehend more easily.…”
Section: Discussionmentioning
confidence: 99%
“…29 Online calculators are useful, cost-free tools that can assist physicians in risk-and-benefit estimations and inform joint decision-making with patients and/or guardians. 17,18,22,[30][31][32] The format of an online calculator renders complex statistical models more accessible with the potential for broad clinical impact. 17,18,22,[30][31][32] The HOPS calculator thus builds on the previously reported HOPS study, which identified five important predictors of post-hemispheric surgery seizure freedom (age greater than 3.5 years at seizure onset, absence of generalized seizure semiology, absence of contralateral FDG-PET hypometabolism, stroke-induced seizure etiology, and absence of prior resective neurosurgery) and developed an easyto-use seizure outcome prediction score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, many prediction tasks appear simply too difficult in the real-world (meaning, with proper external validation)-probably, it is simply unrealistic to expect to be able to predict the future with any great amount of accuracy. 6 Conceptually, this is even clearer in medical prediction modeling: Predicting future outcomes that depend on hundreds of factors would-of course -require collection and integration of these hundreds of factors. Apart from the impracticality of collecting and inputing such wealths of data into an online calculator in daily practice, in medicine, we usually do not even have the case numbers to allow for training of models with hundreds of factors (which would require tens of thousands of patients for proper clinical prediction modeling).…”
mentioning
confidence: 99%